Powering the future: Academic journals and language research - Kenneth N. Beatty (Peoples' Friendship University of Russia (RUDN University), 2022)
The first academic journal was published in 1655 and the first peer-reviewed journal followed in 1731. Since then, academic journals have changed little in form and only slightly in purpose. Academic journals continue to increase exponentially in number in ever-emerging fields, but there are negative washback effects to current journal publication, beginning with the publish and perish principle that works against innovative research objectives, topics and methodologies. Digital technologies now offer new opportunities to rethink the process, role and function of academic journals and, in language education, to overcome typical problems such as limited experimental subject pools, dated data, time constraints, a focus on marginal ideas and static findings. This paper also suggests how academic journals and papers can be improved, particularly in the area of English Language Teaching and the Common European Framework of Reference (CEFR).